2023
DOI: 10.1017/jfm.2023.749
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimisation of mixing in binary droplet collisions

Élfego Ruiz-Gutiérrez,
Josef Hasslberger,
Markus Klein
et al.

Abstract: The collision of binary droplets plays a key role in several industrial, chemical and biological processes. In these processes, the quality of the desired outcome is strongly dependent on the mixing of the liquid droplets as they collide in mid-air. In this work, multiphase direct numerical simulations based on the volume-of-fluid method have been used to investigate the process of mixing and analyse the effects of parameters such as injection velocity, timing and collision angles. The evolution of mixing due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
(85 reference statements)
1
4
0
Order By: Relevance
“…As documented in a previous analysis [6], if the contact surface area lies on the reflection symmetry plane x = 0, the segregation parameter has a high value. Therefore, a large value of the segregation parameter is expected to occur at ν 1 /ν 2 = 1 as both liquids are identical and have been injected with identical conditions.…”
Section: Viscosity Differencessupporting
confidence: 62%
See 4 more Smart Citations
“…As documented in a previous analysis [6], if the contact surface area lies on the reflection symmetry plane x = 0, the segregation parameter has a high value. Therefore, a large value of the segregation parameter is expected to occur at ν 1 /ν 2 = 1 as both liquids are identical and have been injected with identical conditions.…”
Section: Viscosity Differencessupporting
confidence: 62%
“…11 shows that the segregation parameter is the highest for M a = 0, which occurs for equal surface tension between the two liquids. This effect arises, as discussed in the previous subsection, due to the reflection symmetry in the system, forcing the contact surface to remain in the plane of symmetry and thus hampering the mixing of the liquids [6]. However, it can be observed that even small differences in surface tension produce large Marangoni numbers due to the small value of the diffusivity.…”
Section: Viscosity Differencesmentioning
confidence: 95%
See 3 more Smart Citations